CD25+CD4+ regulatory T cells generated by exposure to a model protein antigen prevent allograft rejection: antigen-specific reactivation in vivo is critical for bystander regulation. - Karim, M; Feng, G; Wood, K; Bushell, A (2005)
The importance of CD25(+)CD4(+) regulatory T (Treg) cells in the control of immune responses is established, but their antigen specificity in vivo remains unclear. Understanding Treg-cell specificity requirements will be important if their potential is to be developed for immunotherapy. Pretreatment of recipient mice with donor alloantigen plus anti-CD4 antibody generates CD25(+)CD4(+) Treg cells with the capacity to prevent skin allograft rejection in adoptive transfer recipients. Here we demonstrate that, although this regulation can be antigen-specific, reactivation with the original tolerizing alloantigen allows the Treg cells to suppress rejection of third-party allografts. Aware of the limitations of alloantigen pretreatment, we asked whether graft-protective Treg cells could be generated against unrelated, nongraft antigens. We demonstrate that bystander regulation also extends to CD25(+)CD4(+) Treg cells generated in vivo by exposure to nominal antigens under anti-CD4 antibody cover. Providing these Treg cells are reexposed to the tolerizing antigens before adoptive transfer, they prevent the rejection of fully allogeneic skin grafts. That this might form the basis of a clinically relevant tolerance induction strategy is demonstrated by the fact that, when combined with subtherapeutic anti-CD8 antibody, Treg cells generated in response to nongraft antigens facilitate the acceptance of cardiac allografts in primary recipients.